Methyl Red Based Test Strip for Identification of Formalin Compounds in Fish Samples - Haji, Lina Sun; Anida, Choirun Nisa; Aprilianti, Caleysda; Fauziyyah, Himayah Izmi; Pitaloka, Diah Ayu; Zulfikar, Zulfikar (BERKALA SAINSTEK, 2024)
Methyl red based test strips were introduced a simple method for formalin identification. The test strip was designed based on the feasibility of the formalin oxidation reaction using hydrogen peroxide in an alkaline medium and using the methyl red indicator which is detected at a wavelength of 526 nm, with a concentration range from 1.0 - 10.0 ppm. The test strip was designed by immobilizing methyl red and NaOH in a Whatman paper matrix number 40 for 40 minutes and it has been evaluated by adding formalin samples and oxidator to the surface of the test strip. Optimum measurement conditions were obtained at 0.05 mL of 0.06M methyl red, 0.2 mL of 0.001M NaOH and 0.25 mL of 2% H2O2. The test strip has a good performance to identify formalin in the concentration range of 1.0 - 7.5 ppm which is monitored by a color change from yellow to red. The feasibility of using the test strip is also carried out by analyzing real samples through a recovery test. Test strips still can be used to identify formalin until 30 days when it stored at room temperature, and 2 days when it stored in the refrigerator.